Neoliberal Branding and the Commodification of Language: English as the Language of Success in Advertisements for Language Centre in Pakistan - Khan, Iftikhar; Haidar , Dr. Sham (Register Journal, 2024)
Neoliberalism, an economic system rooted in free markets and market-driven policies, extends the concept of commodities beyond traditional goods to domains such as language. In this framework, the English language is assigned exchange value and is marketed as a commodity within neoliberal economies. This phenomenon is prominently observed in advertisements of language centers, where English is branded as essential for success. Drawing upon Bourdieu's theory of linguistic capital (1991, 1997), this study adopts an interpretivist paradigm and employs qualitative research methods. English language center advertisements were selected through purposive sampling, and Kress and van Leeuwen's multimodal model (2006) serves as the analytical framework. The study finds that language centers actively promote English proficiency as a means to empower individuals in the linguistic marketplace. These advertisements consistently portray English as a language of success, positioning it as a gateway to career advancement and personal development. However, some advertisements also employ tactics to influence potential clients by disseminating accurate information.